The number of clusters on trust - Silvestre, Cláudia (2017)
In this work we analyse the perfomance of a new Expectation Maximization (EM) clustering approach. This method is based on the Minimum Message Lenght (MML) criterion and simultaneously yields clustering of categorical data and the number of clusters. We group European citizens based on their trust in institutions, using Europen Social Survey data. The results obtained illustrate the parsimony, the cohesion-separation and stability of the EM-MML solutions, when compared to traditional information criteria EM based approaches.